The Moderating Effect of Institutional Governance on the Relationship between Public Financial Management and Education Service Delivery in Selected Public Universities in South Sudan - Ring Longar Gum Majok; George Olowo; Charles Ndalu Wasike (East African Journal of Interdisciplinary Studies, 2026)
This study examined the moderating effect of institutional governance on the relationship between public financial management and education service delivery in selected public universities in South Sudan. The inquiry was motivated by evidence that technically sound financial reforms often fail to improve services in contexts of weak governance, a recurrent feature of fragile, post-conflict states. Anchored on Institutional Governance, New Public Management, and Principal-Agent theories, the study adopted a pragmatic paradigm and a convergent parallel mixed-methods design. Data were collected from staff and policymakers at the University of Juba, the University of Bahr El-Ghazal, and Upper Nile University, as well as from the Ministry of Higher Education, Science and Technology. From a distributed sample of 400, an analytic sample of 358 respondents completed a five-point Likert questionnaire, complemented by 21 key informant interviews and three focus group discussions. Internal consistency was very good (Cronbach's alpha of 0.849 for institutional governance and 0.886 for education service delivery). Hierarchical multiple regression showed that the three public-financial-management components explained 41.4 percent of the variance in education service delivery, that adding institutional governance raised this to 45.6 percent, and that adding the interaction terms raised it to 56.2 percent (delta R2 = 0.106, F(7, 350) = 64.03, p < 0.001). Two of the three interactions were significant and the third marginal (budget implementation by governance, beta = 0.142, p = 0.009; budget formulation by governance, beta = 0.126, p = 0.036; budget monitoring by governance, beta = 0.102, p = 0.083), and a Hayes PROCESS Model 1 analysis confirmed that the effect of each component on service delivery strengthened as governance improved. The null hypothesis was therefore partially rejected. Qualitative analysis yielded four themes: leadership as a critical enabler, staff capacity gaps, structural weaknesses, and policy and regulatory gaps. The study concludes that institutional governance is the infrastructure within which financial management operates and recommends pursuing reforms in governance and financial management together.